Is collaborative housing (really) for all? Bridging the gap towards inclusive collaborative housing in the Lisbon Metropolitan Area - Farias, A. C. C.; Lages, J.; Saaristo, S.-M. (ENHR Conference 2024: Making Housing Systems Work, 2024)
Collaborative housing has been an emerging topic in European housing studies. The housing crisis, combined with an appeal to a sustainable lifestyle wrapped in an atmosphere of creativity, has contributed to the middle class's crescent adoption of this model, less spread among more disadvantaged groups. Our proposal discusses the use of collaborative housing models, with care as a driver, for urban poor living in housing precarity. Based on the Lisbon Metropolitan Area, this proposal debates how to facilitate the introduction of co-housing models to communities living in a context of precarity. First, a community-led survey was conducted, empowering dwellers with updated knowledge of their own socio-spatial reality. Afterwards, workshops were designed to assess how communities are alike in sharing domestic activities. The results show great potential for the collectivisation of domestic space and self-organisation, making a collaborative housing model viable, when addressing relocations of disadvantaged communities.